The making of the GDR : 1945 - 53 ; from antifascism to Stalinism - Pritchard, Gareth (Manchester Univ. Press, 2000)
"The making of the GDR 1945-53 develops an analysis of the Stalinisation of East Germany in the period of 1945 to 1953. This book focuses on the social roots of the emerging dictatorship. The making of the GDR 1945-53 also tells a human story, in which the aspirations of antifascists and Socialists were manipulated and ultimately betrayed by Stalinism." "The analysis developed in this book is based on extensive research in the newly available East German archives. It will be of interest to those concerned with the division of Germany, the nature of the GDR, and the whole trajectory of post-war German politics."--BOOK JACKET.